Underdiagnosis, false diagnosis and treatment of COPD in a selected population in Northern Greece. Issue 1 (1st January 2021) - Spyratos, Dionisios; Chloros, Diamantis; Michalopoulou, Dionisia; Tsiouprou, Ioanna; Christoglou, Konstantinos; Sichletidis, Lazaros
Abstract: Background: In the primary care setting, diagnosis and treatment of COPD is not always consistent with GOLD guidelines. Objectives: To calculate the prevalence of COPD underdiagnosis, false diagnosis and treatment in the general population of northern Greece. Methods: Observational study in the context of an early COPD detection and smoking cessation project. Inclusion criteria: >40-year-old, current and former smokers (>10 pack-years) in five primary care centres of northern Greece from 2012 to 2019. Participation was achieved via a campaign (posters and advertisements in the mass media). Results: We examined 5, 226 subjects (mean age: 58.2 ± 12.7 years, 61.5% males, current smokers: 56.2%) of whom 564 (10.8%) had symptoms and spirometrically confirmed COPD. There were 5 groups of 'interest:' a) 117/264 (44.3%) with a previous correct diagnosis COPD and correct treatment; b) 139/264 (52.7%) previous correct diagnosis COPD but overtreatment; c) 8/264 (3%) previous correct diagnosis COPD but undertreatment; d) 461 subjects (63.6% of those with previous COPD diagnosis) had previous false diagnosis of COPD (= also overtreatment); e) 300/564 (53.2%) previously not diagnosed COPD (=underdiagnosis and also undertreatment). We found that 322/461 (69.8%) of those with a previous false diagnosis have been prescribed long-acting bronchodilators plus ICS. Conclusion: Among the general population subjects in northern Greece, more than 50% of patients with COPD were underdiagnosed, more than 50% of correctly diagnosed COPD patients were overtreated and most patients taking inhaled drugs were those with a false diagnosis of COPD (possibly GOLD stage 0).